Handbook of neurotoxicity - Kostrzewa, Richard M. (Springer New York, 2014)
The Handbook of Neurotoxicity is a reference source for identifying, characterizing, instructing on use, and describing outcomes of neurotoxin treatments - to understand mechanisms associated with toxin use; to project outcomes of neurotoxin treatments; to gauge neurotoxins as predictors of events leading to neurodegenerative disorders and as aids to rational use of neurotoxins to model disease entities. Neuroprotection is approached in different manners including those 1) afforded by therapeutic agents - clinical and preclinical; or 2) by non-drug means, such as exercise. The amorphous term 'neurotoxin' is discussed in terms of the possible eventuality of a neuroprotectant producing an outcome of excess neuronal survival and a behavioral spectrum that might produce a dysfunction - akin to a neurotoxin's effect. The Handbook of Neurotoxicity is thus an instructive and valuable guide towards understanding the role of neurotoxins/neurotoxicity in the expansive field of Neuroscience, and is an indispensable tool for laboratory investigators, neuroscientists, and clinical researchers.